RESEARCH OF THE PHYSICAL DEVELOPMENT OF BASKETBALL STUDENTS FROM SOFIA UNIVERSITY ST. “KLIMENT OHRIDSKI” - I. Peltekova (Trakia Journal of Sciences)
The article presents the results of the measurements made on the physical development of students who have chosen basketball as a compulsory discipline. The measurements include height, weight, and body mass index (BMI). All participants in the study are students from Sofia University, a regular form of education. Students are in age between 18 and 26, from different faculties and disciplines. The results are based on gender and age. Two measurements were made-Test 1 and Test 2 (T1 and T2). According to the results of BMI, the students are divided into four categories: “healthy range”, “lower than healthy”, “overweight” and “obesity”. According to the results obtained in BMI calculation, it was found that in T1 for women and men 66.2 % of the students were in a “healthy range”, ranked on the index of obesity. In T2 the percentage increased to 68.8%. 14.3 % of the students have “lower than healthy” weight. For women this percentage is higher-18.2% compared to men 11.4 %